CONTRIBUTION TO THE KNOWLEDGE OF GALL-INDUCING INSECTS IN THE AMAZON FOREST - GRANDEZ-RIOS, Julio Miguel (2024)
Little is known about galling insects in the Amazonian rainforest, despite its renown as a highly biodiverse ecosystem. In an effort to fill this knowledge gap, we compiled data from existing studies of gall-inducing insects and their host plants in the Amazon biome. A total of 32 studies focusing on insect galls and their host plants in the Amazon were assessed. Taxonomy, inventory, and ecology emerged as the most prominently represented areas of investigation. We found 31 species of Cecidomyiidae, from seven tribes and 21 genera, reported in the Amazon Forest. The richness of gall-inducing insects exhibited a positive correlation with the size of their associated plant families, while showing no significant correlation with the age of those families.